The Prohibition of Collective Expulsion : Protecting against Arbitrary Expulsion in Human Rights Treaty Law - Riemer, Lena (Human Rights and Humanitarian Law E-Books Online, Collection 2026., 2025)
The Prohibition of Collective Expulsion: Protecting against Arbitrary Expulsion in Human Rights Treaty Law examines this fundamental safeguard as a cornerstone of migrants' rights. Without effective procedural guarantees, other protections remain meaningless in the border context. In her book, Lena Riemer explores how the prohibition of collective expulsion ensures due process for migrants and asylum seekers across international and regional human rights systems, from the European and Inter-American Conventions to the African Charter and the Migrant Worker Convention. Through a holistic analysis of jurisprudence, the book highlights the principle's critical role in preventing arbitrary expulsions.